2017
DOI: 10.1136/bmjopen-2016-013661
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis: Tai Chi for preventing falls in older adults

Abstract: ObjectiveIt remains unclear whether Tai Chi is effective for preventing falls in older adults. We undertook this systematic review to evaluate the preventive effect of Tai Chi by updating the latest trial evidence.DesignSystematic review and meta-analysis.MethodsThe Cochrane Library, MEDLINE and EMBASE were searched up to February 2016 to identify randomised trials evaluating Tai Chi for preventing falls in older adults. We evaluated the risk of bias of included trials using the Cochrane Collaboration's tool. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
120
3
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(144 citation statements)
references
References 31 publications
(72 reference statements)
4
120
3
5
Order By: Relevance
“…We identified five guidelines and six systematic reviews [5,[14][15][16][17][18] that addressed fall interventions in the outpatient setting, and three guidelines and three systematic [15,19,20] reviews related to fall interventions in the inpatient setting (some overlap exists). An overview of these guidelines and their level of evidence can be found in Supplementary Tables 1 and 2.…”
Section: Fall Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified five guidelines and six systematic reviews [5,[14][15][16][17][18] that addressed fall interventions in the outpatient setting, and three guidelines and three systematic [15,19,20] reviews related to fall interventions in the inpatient setting (some overlap exists). An overview of these guidelines and their level of evidence can be found in Supplementary Tables 1 and 2.…”
Section: Fall Interventionsmentioning
confidence: 99%
“…Exercise is the second most commonly recommended intervention from the guidelines. Group and homebased exercise training incorporating balance, gait, and strength training [5] and Tai Chi [14] have been found to be effective in preventing falls. Exercise activity/programs should be titrated according to the person's current functional level and abilities [22].…”
Section: Interventions -Outpatientmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, several studies of various effects of Tai Chi exercise have been published. Systematic reviews have concluded that there is convincing evidence for the positive effects of Tai Chi on fall prevention (Huang, Feng, Li, & Lv, ), depressive symptoms (Chi, Jordan‐Marsh, Guo, Xie, & Bai, ) and cognitive performance (Wayne et al., ) among older people. Tendencies to improve physical performance by Tai Chi exercise was found in chronic conditions such as heart failure and chronic obstructive pulmonary disease (Chen, Hunt, Campbell, Peill, & Reid, ).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity or exercise (one domain of physical activity) intervention programs have been shown to delay age-related balance or cognitive decline (Chase et al, 2016;Zou et al, 2017a;Gheysen et al, 2018;Zhang et al, 2018). Tai Chi (TC) has been recognized to promote both fall-related balance ability and cognitive function in the aging population (Wayne et al, 2014;Huang et al, 2017). TC Is a mind-body exercise with special features that have shown to be effective for improving balance and cognition together.…”
Section: Introductionmentioning
confidence: 99%